Perfil do atendimento de adolescentes em uma Unidade de Pronto Atendimento - Cortez, Lúcia Elaine Ranieri; Correa, Ana Paula Rondina; Alberti, Nathália Luz; Silva, Eraldo Schunk [UNESP]; Yamaguchi, Mirian Ueda (My University, 2017)
Objective: Characterize the medical records of adolescents in an emergency unit regarding morbidity, day of the week, hour and risk classification. Methods: This is a descriptive and retrospective research which data collected by manual analyses of medical records of teenagers in the emergency unit (UPA) from January 1, 2014 to January 31, 2014. The morbidity profile was classified according to the International Classification of. Information was synthesized using frequency tables and associations between CID - 10 cause groups and socio-demographic variables were tested by using the Chi-square test (χ2) and Fisher's Exact test. Results: There were 1052 records, in which 54.94% were female and 45.06% were male and 76.56% of the visitors had between 15 to 19 years. The majority of visits occur during (55.59%) and infectious and parasitic diseases were the prevalent causes of diseases. Regarding the risk classification, the green color was the most prevalent in 77.26%.
Profile of adolescent’s care in an emergency unit
Keywords: Adolescent; Emergency medical services; Triage